The influence of the key limiting factors on the limitations of heat transfer in heat pipes with various working fluids - Р. С. Мельник; Ю. Є. Ніколаєнко; В. Ю. Кравець; Є. С. Алексеїк (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Aluminium and copper heat pipes with grooved and metal fibrous capillary structure are high effective heat transfer devices. They are used in different cooling systems of electronic equipment like LED modules, microprocessors, receive-transmit modules and so on. However, thus heat pipes have heat transfer limitations. There are few types of these limitations: hydraulic limitation, boiling limitation, liquid entrainment by vapor flow and sonic limitation. There is necessity to know which one of these limitations is determinant for heat pipe due to design process. At a present article calculations of maximum heat transfer ability represented. All these calculations were made for LED cooling by using heat pipes with grooved and metal fibrous capillary structures. Pentane, acetone, isobutane and water were used as a coolant. It was shown that the main operation limit for axial grooved heat pipe, which determinate maximum heat transfer ability due to inclination angle for location of cooling zone higher than evaporation zone case, is entrainment limit for pentane and acetone coolants. Nevertheless, for isobutane coolant the main limitation is a boiling limit. However, for heat pipes with metal fibrous capillary structure the main limitation is a capillary limit. This limitation was a determinant for all calculated coolants: water, pentane and acetone. For high porosity range of capillary structure, capillary limit transfer to sonic limit for heat pipes with water, that means that the vapor velocity increases to sonic velocity and can't grow anymore. Due to this, coolant can't in a needed quantity infill condensation zone and the last one drained. For heat pipes with acetone and pentane, capillary limit transfer to boiling limit. All calculations were made for vapor temperature equal to 50°C, and for porosity range from 30% to 90%.